The Inhibitory Role of M2000 (β-D-Mannuronic Acid) on Expression of Toll-like Receptor 2 and 4 in HT29 Cell Line - Sharifi, Laleh; Moshiri, Mona; Dallal, Mohammad M.S.; Asgardoon, Mohammad H.; Nourizadeh, Maryam; Bokaie, Saied; Mirshafiey, Abbas (Recent Patents on Inflammation & Allergy Drug Discovery, 2019)
Background/Objectives: Anti-inflammatory agents play a crucial role in controlling inflammatory diseases such as Inflammatory Bowel Disease (IBD) but their use is restricted due to their vast side effects. M2000 (β-D-mannuronic acid) is a new immunomodulatory drug. According to the capacity of M2000 in suppressing some molecules involved in Toll Like Receptors (TLRs) signaling and reducing oxidative stress we hypothesize that, this molecule may have a potential role in decreasing inflammatory responses in IBD. The aim of this study was to evaluate the cytotoxicity of M2000 and its effect on the gene expression of TLR2 and TLR4. Methods: HEK293 cell line was grown and divided into 96-well cell plate and MTT assay was performed. HT29 cells were cultured and treated with low and high doses of M2000. Total RNA was extracted and cDNA synthesized and quantitative real-time PCR was done to quantify the TLR2 and TLR4 mRNA expression. Results: We found that M2000 at the concentration of ≤ 1000μg/ml had no obvious cytotoxicity effect on the HEK293 cells. Also, low and high doses of M2000 could significantly down-regulate both TLR2 and TLR4 mRNA expression. Moreover, a significant reduction in gene expression of TLR2 and TLR4 in an inflammatory condition resulted in high doses of M2000 in the presence of LPS. Conclusion: Our study which was conducted in colonic epithelial cell model, shows that M2000 can be considered as a new anti-inflammatory agent in IBD. However, more comprehensive experimental and clinical studies are required to recognize the molecular mechanism of M2000 and also its safety and efficacy.
Keywords: M2000